Das Denken der Lehre: Walter Benjamin, Franz Joseph Molitor and the Jewish tradition - Mertens, Bram (2001)
This thesis is a dialectical exploration of the importance of the Jewish tradition and theology in the work of Walter Benjamin, primarily through his reading of Franz Joseph Molitor's Philosophie der Geschichte oder über die Tradition, and secondarily through his close friendship with Gershom Scholem. It also argues that the influence of the Jewish tradition is a constant factor in Benjamin's work, transcending the conventional division between his 'metaphysical' Frühwerk and his 'Marxist' Spätwerk.